Оn pulsating radiation in weakly inverted media - Kirichok, A.V.; Kuklin, V.M.; Mischin, A.V.; Zagorodny, A.G. (Вопросы атомной науки и техники, 2018)
A change in the character of maser generation in a two-level system is found when the initial population inversion exceeds some threshold value equal to the square root of the total number of atoms. Above this threshold, the number of photons begins to grow exponentially with time and the pulse with short leading edge and broadened trailing edge is generated. In this work, we attempt to explain the nature of this threshold. Coherent pulse duration, estimated by its half-width, increases significantly with increasing inversion, if all other parameters are fixed and the absorption is neglected. The inclusion of the energy loss of photons leads to the fact that the duration of coherent pulse is almost constant with increasing inversion, at least well away from the threshold. If there is a mechanism for restoring population inversion, a pulsating regime for generating stimulated emission becomes possible. The integral radiation intensity at this can be increased several times. This approach can be used to analyze cosmic radiation, which could help explain the great diversity of pulsating radiation sources in space. Розглянуто зміну характеру генерації в дворівневій системі, коли початкова інверсія населеності перевищує порогове значення, яке дорівнює квадратному кореню із загальної кількості станів. Вище цього порога генерується імпульс з коротким переднім фронтом і розширеним заднім фронтом. Тривалість когерентного імпульсу, оцінююча за його напівшириною, значно зростає зі збільшенням інверсії, якщо всі інші параметри фіксовані і поглинання нехтується. Включення втрат енергії фотонів призводить до того, що тривалість
когерентного імпульсу майже постійна зі збільшенням інверсії, принаймні, далеко від порогу. Якщо існує
механізм відновлення інверсії заселеності, стає можливим пульсуючий режим генерації вимушеного випромінювання. Інтегральна інтенсивність випромінювання при цьому може бути збільшена в декілька разів.
Цей підхід може бути використаний для аналізу космічного випромінювання, яке могло б допомогти пояснити велику різноманітність пульсуючих джерел випромінювання в космосі. Рассмотрено изменение характера генерации мазера в двухуровневой системе, когда начальная инверсия
населенности превышает некоторое пороговое значение, равное квадратному корню из общего числа состояний. Выше этого порога генерируется импульс с коротким передним фронтом и расширенным задним
фронтом. Длительность когерентного импульса, оцененная по его полуширине, значительно возрастает с
увеличением инверсии, если все остальные параметры фиксированы и поглощение пренебрегается. Включение потери энергии фотонов приводит к тому, что длительность когерентного импульса почти постоянна с
увеличением инверсии, по крайней мере, далеко от порога. Если существует механизм восстановления инверсии населенностей, становится возможным пульсирующий режим генерации вынужденного излучения.
Интегральная интенсивность излучения при этом может быть увеличена в несколько раз. Этот подход может быть использован для анализа космического излучения, которое могло бы помочь объяснить большое
разнообразие пульсирующих источников излучения в космосе.